Optimization of a DNA extraction method using Subepidermis from Austrocylindropuntia and Opuntia-Opuntioideae (2022)
The taxonomic identification of species through analysis of the variation of orthologous DNA sequences, complement the information obtained with morphological characters. Cytogenetic studies indicate that polyploid taxa occur in the subfamily Opuntioideae, Opuntia ficus-indica, contributing to morphological variability in the individuals of a population, and influencing the correct identification of species. However, the lengths of the sequences in Opuntioideae are affected by the extraction of pure DNA. Different extraction methods were evaluated and modified, and a procedure was established to obtain good quality DNA, free of inhibitors for gene amplification by polymerase chain reaction. The ratio A260/A280 and A260/A230 ranged from 1.6 to 2.1, revealing absence of contamination with the modified protocol for DNA extraction from cotton leaves. This method is inexpensive compared to those of commercial manufacturers and, therefore, can be applied in studies with limited resources.